GEOPOLITICAL AND ECONOMIC POTENTIAL OF THE EURASIAN ECONOMIC UNION SPACE AND COUNTRIES OF THE CASPIAN REGION - E. E. Golovina (Современная наука и инновации, 2023)
A general description of the countries of the Eurasian Economic Union and the Caspian region is given, their place in the modern world, taking into account the economic significance and international relations. New geopolitical concepts have been introduced: Big Caspian Five; The Caspian (Caspian) five and the Eurasian rhombus, uniting countries close in their views on modern trends in the development of new world economic relations. For individual countries of the Caspian (Caspian) five, a SWOT analysis was performed in relation to their "international positions" (IP) in the region, their strengths were identified, which should be taken into account when assessing their IP, planning Russia's foreign policy. An analysis of the weaknesses of the Caspian states made it possible to assess the potential of their "vulnerability" in relation to possible adverse impacts. The threats associated with the actions of internal and external actors are considered. The possibilities of states are analyzed, including the possibility of strengthening their international positions in the zone of the Caspian region and in the world. It is substantiated that the Eurasian Economic Union, as an international organization, acts as a middle space within which global projects are formed that have a new integration development potential. Within the framework of this configuration, approaches to linking the most important segments of the development of the EAEU countries and the Caspian region and the area of the modern geopolitical project "Great Caspian" are substantiated.